1971
DOI: 10.1172/jci106622
|View full text |Cite
|
Sign up to set email alerts
|

The human alveolar macrophage: isolation, cultivation in vitro, and studies of morphologic and functional characteristics

Abstract: A B S T R A C T Human alveolar macrophages were lavaged from surgically resected lungs and from lungs of normal subjects. Macrophages that had been purified by glass adherence were maintained in tissue culture for as long as 54 days. After 3-4 wk in vitro they underwent transformation into multinucleated giant cells. These aged cells had more than 30 times the phagocytic capacity that the same group of cells had had after 1 day in vitro.Phagocytosis of heat-killed Candida albicans was inhibited by iodoacetate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(72 citation statements)
references
References 17 publications
6
66
0
Order By: Relevance
“…The resistance of L. pneumophila to killing is perhaps in part due to a low in vitro antibacterial capacity of alveolar macrophages relative to other phagocytes. Although alveolar macrophages in vitro ingest and kill a variety of potential pulmonary pathogens (S. aureus, E. coli, T. gondii, S. pneumoniae, L. monocytogenes, N. asteroides, and K. pneumoniae), their bactericidal capacity against a given target organism is low compared with other phagocytes (17,19,24,(26)(27)(28)(29). Similarly, in our study, alveolar macrophages were unable to reduce CFU of E. coii below the level of the original inoculum, whereas monocytes were able to reduce CFU of E. coli by two logs (99%) in the same assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance of L. pneumophila to killing is perhaps in part due to a low in vitro antibacterial capacity of alveolar macrophages relative to other phagocytes. Although alveolar macrophages in vitro ingest and kill a variety of potential pulmonary pathogens (S. aureus, E. coli, T. gondii, S. pneumoniae, L. monocytogenes, N. asteroides, and K. pneumoniae), their bactericidal capacity against a given target organism is low compared with other phagocytes (17,19,24,(26)(27)(28)(29). Similarly, in our study, alveolar macrophages were unable to reduce CFU of E. coii below the level of the original inoculum, whereas monocytes were able to reduce CFU of E. coli by two logs (99%) in the same assay.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of a stained cytocentrifuged sample from each lavage revealed that '90-95% of the cells were macrophages of various sizes; the remaining cells were monocytes, lymphocytes, eosinophils, polymorphonuclear leukocytes, and a few bronchial or oral epithelial cells. As it was difficult to distinguish between monocytes and small alveolar macrophages, additional cytocentrifuged samples were stained for myeloperoxidase (16,17). On the average, 95% of these cells were myeloperoxidase negative (alveolar macrophages) and 5% myeloperoxidase positive (monocytes, granulocytes).…”
Section: Methodsmentioning
confidence: 99%
“…Differentiated macrophages of human or rodent origin lack the capacity to generate certain potent ROS species via myeloperoxidase, used by other phagocytes such as neutrophils. However, they can generate hydrogen peroxide through the nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase system [23,24] and ROS via their mitochondria [25]. They can form more potent microbicidal factors though the reaction of ROS with NO generated through the inducible nitric oxide synthase (NOS2/iNOS) system [26].…”
Section: Macrophage Adaptation To Functionmentioning
confidence: 99%
“…Although composed predominantly of macrophages, the cell populations obtained by bronchopulmonary lavage' of several mammalian species, including man, contain morphologically identifiable lymphocytes (7,9,10). After antigenic stimulation of the respiratory tract, cells appear in alveolar spaces, and these have been reported to be capable of both specific antibody synthesis (11) cell) 2 funictionl, anid cell-milediaited imimiunity (6)(7)(8), a thymus-dependent lymplhocyte (,T cell) funiction.…”
Section: Introductionmentioning
confidence: 99%